Hofmann type clathrates – spectroscopic studies of the low frequency region - Minčeva Šukarova, B.; Andreeva, L.; AKYÜZ, SEVİM (Elsevier, 2007)
A series of Hofmann type clathrates with a general formula: M(NH3)2M′(CN)4·2G, where M ∈ {Ni, Mn, Cd}, M′ ∈ {Ni, Pd}, while G is benzene or thiophene, were prepared and their Raman and far-infrared spectra were recorded in the region 650–50 cm−1. The main bands of the vibrational spectra in the low frequency region were assigned to the stretching and deformational vibrations: ν(Ni–C)/ν(Pd–C), δ(NiCN)/δ(PdCN), π(NiCN)/π(PdCN), δ(CNiC)/δ(CPdC), ν(M–N) and δ(NMN) originating from the host lattices: M(NH3)2Ni(CN)4 or M(NH3)2Pd(CN)4. The Raman and far-infrared spectra of the studied Hofmann type clathrates were compared with the corresponding spectra of K2Ni(CN)4 and K2Pd(CN)4 as well as with Ni(NH3)6Cl2, and in some cases, with the spectra of the “empty” clathrates.
Keywords: Hofmann type clathrates; Raman spectra; Far-infrared spectra; Tetracyanometallate complexes; Hexaamine complexes